As marcas culturais das festas populares no fotojornalismo dos periódicos Correio da Manhã e Tribuna do Norte - Souza, Elmano Ricarte de Azevedo (2014)
This research is about the cultural marks and meanings production on the popular culture context, in honor of Catholics Saints of June: Saint Antony; Saint John and Saint Peter (with celebrations in June 13th, 24th and 30th respectively). These marks are find on the newspapers’ photography of Tribuna do Norte (Natal, Rio Grande do Norte, Brazil) and Correio da Manhã (Lisbon, Portugal). All the photos were published in June 2012. The analysis has theory and methodology in Folkcommunication and in Sociocultural Photocatography. The investigation has focus in the meanings of these marks on the photojournalism about the popular parties and their practices. The study observes also a common view to report about popular culture, which has the influence of a hegemonic paradigm that considers itself the only true one.